Ethics roundtable: choice and autonomy in obstetrics - Wilkinson, D; Teli, S; Litchfield, C; Madeley, A; Kelly, B; Impey, L; Brown, R; Kingma, E; Turnham, H (BMJ Publishing Group, 2024)
Decisions about how and where they deliver their baby are extremely important to pregnant women. There are very strong ethical norms that women’s autonomy should be respected, and that plans around birth should be personalized. However, there appear to be profound challenges in practice to respecting women’s choices in pregnancy and in labour. Choices carry risks and consequences – to the woman and her child; also potentially to her caregivers and to other women. What does it mean for women’s autonomy be respected in obstetrics? How should health professionals respond to refusals of treatment or to requests for care outside normal guidelines? What are the ethical limits to autonomy? In this clinical ethics roundtable, service users, midwives, obstetricians, philosophers and ethicists respond to two hypothetical cases drawn from real-life scenarios.